The Difference of the Learning Environment Perception in Introvert and Extrovert Student in the Faculty of Medicine UNS - Maharani, Dewi Nur; Afifah, Zulaika Nur; Randita, Amandha Boy Timor (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Introduction: An educational institution can be said to be have a certain quality if it is able to provide an effective learning environment so that produce graduates competent doctor. Students perceptions of the learning environment is influenced by many factors, including the type of personality. A student personality type will determine the variation patterns of behavior learning. This research aimed to determine differences in perceptions of the learning environment between the two types of personality. Methods: This research was an observational analytic with cross-sectional approach. Selection of research sample was begun with a preliminary study using Eysenck Personality Inventory (EPI) questionnaire for some Medical students of UNS to know the proportion of students with introvert personality type and students with extrovert personality type. The result was 2 : 3. Population of the research was Medical Students of UNS. The sampling technique was proportional stratified random sampling. There were 276 students obtained as samples. Samples weregiven a Dundee Ready Educational Environment Measure (DREEM) questionnaire. The data obtained were analyzed with the Mann-Whitney test. Results: The results showed a significant difference between the perceptions of the learning environment of introvert and extrovertâs students (p = 0.001). Significant differences contained in the Studentâs Perception of Learning subscale (SPL, p = 0.004), Studentâs Academic Self-Perceptions subscale (SASP, p = 0.000), Studentâs Perception of Atmosphere subscale (SPA, p = 0.003), and the Studentâs Social Self Perception subscale (SSSP, p = 0.001). While, on the Studentâs Perception of Teacher subscale was not found significant difference (SPT, p = 0.381). Conclusions: There was difference of learning environment perception between introvert and extrovert student of personality types. Keywords: perceptions, learning environment, personality types, medical student